Understanding Nigeria’s antibiotic resistance crisis among neonates and its future implications - Victor Oluwatomiwa Ajekiigbe; Ikponmwosa Jude Ogieuhi; Temiloluwa Adebayo Odeniyi; Praise Oluwatobi Ogunleke; Josiah Temitope Olatunde; Adedoyin Veronica Babalola; Akintunde Abisoye Omoleke; Tolulope Felix Omitade; Damilare Emmanuel Olakanmi; Adewunmi Akingbola; Chidera Stanley Anthony (Discover Public Health)
Abstract A well-documented mounting public health crisis is the antibiotic crisis, which is most significantly felt in low-resource countries like Nigeria. This article sheds light on the rising level of antibiotic resistance in newborns in Nigeria, a trend that poses a severe threat to neonatal survival and public health at large. A thorough database search was carried out using terms associated with antibiotic resistance in Nigerian neonates, including PubMed, Google Scholar, and other scholarly sources. Only original research conducted between the start of the study and June 2024 was included; articles without an English translation were not. Independent reviewers handled data management and screening. There has been an increasing prevalence of sepsis among newborns primarily due to Gram-negative bacteria, which highlights the urgency and need to be addressed. Studies show a significant rise in multi-drug-resistant infections, with almost half of Escherichia coli and 86% of Staphylococcus aureus strains among newborns resistant to conventionally used antibiotics like penicillin. Some reasons for the continuous trend include but are not limited to unregulated antibiotic purchase and use, inadequate surveillance systems, and cultural determinants and socioeconomic issues. Effective strategies are needed to curb the neonatal antibiotic crisis in Nigeria. This problem can be mitigated by enhancing public education, strengthening healthcare infrastructure, advocating for better maternal health, and promoting the rational use of antibiotics. Additionally, more research into non-antibiotic medications and understanding the barriers to compliance need to be addressed.